Urban Geography Evolving: Toward an Evolutionary Urban Geography - Weaver, Russell C. (Quaestiones Geographicae, 2014)
Despite growing interest in the application of evolutionary concepts to research questions in human geography, the literature is largely characterised by metaphors or analogies that are disconnected from a broader evolutionary theoretical framework. This paper takes initial steps toward developing such a framework for the subfield of urban geography by defining critical elements and relationships from Darwinian and multilevel selection theories. It then synthesises those components in an application to the issues of urban blight and disorder, to demonstrate how an evolutionary understanding of urban spatial phenomena - an “evolutionary urban geography” - can produce new insights for managing complex processes.